2018
DOI: 10.1177/0731948718790062
|View full text |Cite
|
Sign up to set email alerts
|

A National Online Survey of South Korean High School Students’ Understanding of Learning Disabilities

Abstract: Social consensus has changed the concept of disability in recent decades. For example, in 2001, the World Health Organization (WHO) revised the definition of and terms related to disabilities in the International Classification of Functioning, Disability, and Health (ICF), which is a classification system for health and disabilities. Because health and disability occur in specific contexts, ICF emphasized environmental factors such as "the physical, social and attitudinal environment in which people live and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, in South Korea, there is no clear legal rule to include dyslexia or dyscalculia under the definition of learning disability. Some researchers, however, have insisted that dyslexia should be considered as a characteristic of students with learning disabilities and that appropriate special education supports should be provided for them (e.g., Kim, Kim, Kim, et al., ; Lee and Shin, ). In this respect, it is necessary to investigate the broad operational definition of students struggling to learn mathematics, including those who have learning difficulties, in inclusive settings.…”
Section: Status Of Students Struggling To Learn Mathematicsmentioning
confidence: 99%
“…However, in South Korea, there is no clear legal rule to include dyslexia or dyscalculia under the definition of learning disability. Some researchers, however, have insisted that dyslexia should be considered as a characteristic of students with learning disabilities and that appropriate special education supports should be provided for them (e.g., Kim, Kim, Kim, et al., ; Lee and Shin, ). In this respect, it is necessary to investigate the broad operational definition of students struggling to learn mathematics, including those who have learning difficulties, in inclusive settings.…”
Section: Status Of Students Struggling To Learn Mathematicsmentioning
confidence: 99%
“…Another study found that a course on disability had a limited effect on students' attitudes towards disability (de Boer et al, 2014). Lee and Shin (2019) found that there was no difference in attitudes between students with and without knowledge about learning disabilities as a type of disability. In contrast to these results, another study found that a course on disability was associated with more positive attitudes towards disability (Al-Kandari, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…In O. Lee and Shin's (2019) study, most high school respondents said they knew about or had heard the term dyslexia, but did not know about LD or other subcategories of LD (e.g., mathematics and writing LD). This dichotomous familiarity with LD terminology is a problem.…”
Section: Issue 3 the Public's Limited Understanding Of Ldmentioning
confidence: 98%
“…Furthermore, studies have shown that high school and college students have a limited understanding of LD, and do not know how to interact with their peers with LD (J. Cho, E. Kim, & J. Lee, 2014;O. Lee & Shin, 2019;W.…”
Section: Issue 3 the Public's Limited Understanding Of Ldmentioning
confidence: 99%